2010
DOI: 10.1248/bpb.33.604
|View full text |Cite
|
Sign up to set email alerts
|

Red Ginseng Saponin Extract Attenuates Murine Collagen-Induced Arthritis by Reducing Pro-inflammatory Responses and Matrix Metalloproteinase-3 Expression

Abstract: Ginseng, the root of Panax ginseng C. A. MEYER, has been used as a food product and medicinal ingredient. In this study, we assessed the anti-arthritic effects of red ginseng saponin extract (RGSE), including ginsenosides Rg3, Rk1 and Rg5 as major components, on a murine type II collagen (CII)-induced arthritis (CIA), which is a valid animal model of human arthritis. Oral administration of RGSE at 10 mg/kg reduced the clinical arthritis score and paw swelling in the CIA mice, and inhibited joint space narrowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 34 publications
3
40
0
Order By: Relevance
“…The present study showed that CK attenuated disease activity in CIA mice, both preventively and therapeutically. In previous studies on the effect of ginsenosides on CIA, ginsenosides administration was initiated 18 to 26 days after the first immunization [5,6,8,9]. Consistent with these studies, our data showed that CK was prophylactically effective in suppressing progression of arthritis in the CIA model.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study showed that CK attenuated disease activity in CIA mice, both preventively and therapeutically. In previous studies on the effect of ginsenosides on CIA, ginsenosides administration was initiated 18 to 26 days after the first immunization [5,6,8,9]. Consistent with these studies, our data showed that CK was prophylactically effective in suppressing progression of arthritis in the CIA model.…”
Section: Discussionsupporting
confidence: 89%
“…Meyer, have anti-arthritic or chondroprotective effects [5][6][7][8][9][10][11][12][13][14]. However, the bioavailability of ginsenosides and their metabolites after oral administration was very low [15].…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenosides are considered the major active ingredients of ginseng (Ouyang et al, 2014;Zhao et al, 2014). Ginseng saponins have various pharmacologic effects, such as antioxidation, antitumor, anti-inflammatory activities, and neuroprotective effects (Attele et al, 1999;Radad et al, 2006;Kim et al, 2010). A recent investigation suggested that ginseng suppressed key inflammatory players such as cyclooxygenase (COX)-2, inducible nitric oxide synthase (iNOS), and NF-kB (Park et al, 2009;Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This disease can rapidly progress into multisystem inflammation with irreversible joint damage, causing premature mortality, disability and compromised quality of life in the industrialized and developing world [3,4]. Currently, the major categories of RA medications used in the clinical setting include disease-modifying anti-rheumatic drugs (DEMARDs), non-steroidal anti-inflammatory drugs (NSAIDs), steroid hormone and biologics (TNF-α antibody and the decoy TNF-α receptor) [5]. Long-term use of these drugs leads to immune system weakness, bone marrow suppression, liver and kidney impairment, gastrointestinal discomfort and cartilage degeneration [6].…”
Section: Introductionmentioning
confidence: 99%